Outsourcing of Logistics Activities in Manufacturing Industry - Ogorelc, Anton; Logožar, Klavdij (Promet - Traffic&Transportation, 2012)
The external supply of logistics se1vices is part of a trend towardoutsourcing non-core logistics activities. The scope ofthird-party logistics may range from a relatively limited combinationof activities (e.g. transportation and warehousing) to acomprehensive set of logistics se1vices.The authors first discuss the characteristics of business logisticsin manufacturing indusfly, to be taken into account inlogistics outsourcing. They particularly point out the motimtionsfor logistics outsourcing, the possibilities of outsourcing,as well as supplier selection. Finally they analyze the outsourcingin the reverse logistics.